1994
DOI: 10.1073/pnas.91.22.10732
|View full text |Cite
|
Sign up to set email alerts
|

In vivo suppression of injury-induced vascular smooth muscle cell accumulation using adenovirus-mediated transfer of the herpes simplex virus thymidine kinase gene.

Abstract: Restenosis, a process characterized in part by excessive smooth muscle cell (SMC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(105 citation statements)
references
References 32 publications
7
96
0
2
Order By: Relevance
“…22,61,62 In contrast to the Ad-Gaxtreated arteries, no discernible difference was seen in the extent of neointima formation between the Ad-CMVluctreated and saline-treated arteries in the control group of animals. The ability of Gax overexpression to inhibit neointima formation compares favorably with previous recent results reported by other groups using adenovirusencoded genes for wild-type and mutant form of RB in rat and porcine models, 46,63 the herpes simplex virus thymidine kinase gene in rat, rabbit and porcine models, 26,27,55,56 p21 53 in the rat model and hirudin in the rat model. 54 Overall, the reduction in intima/media ratio achieved with these agents ranged from 35 to 50%.…”
Section: Enzymes Withsupporting
confidence: 84%
See 1 more Smart Citation
“…22,61,62 In contrast to the Ad-Gaxtreated arteries, no discernible difference was seen in the extent of neointima formation between the Ad-CMVluctreated and saline-treated arteries in the control group of animals. The ability of Gax overexpression to inhibit neointima formation compares favorably with previous recent results reported by other groups using adenovirusencoded genes for wild-type and mutant form of RB in rat and porcine models, 46,63 the herpes simplex virus thymidine kinase gene in rat, rabbit and porcine models, 26,27,55,56 p21 53 in the rat model and hirudin in the rat model. 54 Overall, the reduction in intima/media ratio achieved with these agents ranged from 35 to 50%.…”
Section: Enzymes Withsupporting
confidence: 84%
“…Gene Therapy products acting locally (eg herpes simplex virus 1 thymidine kinase, NO synthase, cytosine deaminase), 26,27,[55][56][57][58][59] have been developed with adenoviral vectors designed to optimize transfection efficiency. A previous report has demonstrated that gene transfer to the neointima 1 month after stent implantation was feasible.…”
Section: Enzymes Withmentioning
confidence: 99%
“…13 Other pro-death strategies have demonstrated efficacy in post-angioplasty restenosis models by overexpression of thymidine kinase. [16][17][18] Wildtype p53 (wt p53) has been shown to promote SMC apoptosis 19 and modulate SMC proliferation, 20 phenotypes that may be beneficial for prevention of neointimal hyperplasia by gene therapy. In this study we document the effect of wt p53 overexpression on human saphenous vein SMC in isolated culture and in an organ culture model of human vein graft neointimal thickening.…”
Section: Introductionmentioning
confidence: 99%
“…One must consider the safety profile of the vector at the dose that would be required for the particular gene candidate. 59 In one sense, the least risky vectors are DNA, 60 followed by nonintegrating viruses such as adenovirus, [61][62][63] and lastly by integrating viruses such as adeno-associated virus 64 and lentivirus. 65,66 Another factor in safety is related to the immune response generated by the vector.…”
Section: Choice Of Delivery Vectormentioning
confidence: 99%